Development and validation of a measure of climate change anxiety. (June 2020) - Clayton, Susan; Karazsia, Bryan T.
Abstract: There is increasing attention to the negative emotional responses associated with awareness of climate change. We present three studies developing a scale of climate change anxiety. In Study 1, the scale was developed and validated in an MTurk sample of 197. Exploratory factor analysis of our item pool revealed a four-factor structure, with cognitive-emotional impairment, functional impairment, behavioral engagement, and experience emerging as unique factors. Cognitive-emotional impairment and functional impairment were considered to constitute subscales for climate change anxiety; along with behavioral engagement, they were all related to experience as well as to negative emotions. Neither climate change anxiety nor general depression and anxiety were related to behavioral engagement. Study 2 replicated the factor structure as well as the pattern of correlations in a second MTurk sample of 199. Study 3 examined the relationship between climate change anxiety and adaptation responses in a sample of 217, and tested whether climate change anxiety scores would be affected by the framing of a climate change message. Overall, results suggest that climate change anxiety is not uncommon, especially among younger adults; that worry can be differentiated from a more serious impact on one's life; and that climate change anxiety is correlated with emotional but not behavioral responses to climate change. Highlights: A measure of climate change anxiety demonstrated similar structure and correlations in two samples. Climate change anxiety included cognitive and functional impairment factors. Behavioral engagement was uncorrelated with climate anxiety. Climate anxiety, but not behavioral engagement, was associated with a general measure of depression and anxiety. Younger adults showed higher levels of climate anxiety.